Sistem Pakar Deteksi Dini Stunting pada Balita - Adelia, Valentin; Pingky A. R. L. Lede (Lembaga Pengembangan Kinerja Dosen, 2023)
Unmet nutritional needs can potentially affect the future growth of toddlers. One pf the consequences is stunting, which refers to failure in the growth of a child’s body and brain due to prolonged malnutrition. To assess the nutritional status of toddlers, parents usually consult nutrition experts. However, there are various factors that may prevent them from seeking such consultations, including a lack of experts or specialists, economic constraints, and busy schedules. This research aims to develop an early detection expert system for identifying stunting in toddlers, providing parents with the convenience of early detection at any time. The method employed in this study is forward chaining, a reasoning approach where users can select symptoms or characteristics, which will then be concluded as a diagnostic result. The outcame of this research is a web-based expert system for early detection of stunting in toddlers, which can be utilized by parents to identify stunting in their children at an early stage.